Pedagogical stereotypes in professional activities: «for» and «against». (Journal of Educational Sciences, 2016)
In the article the types of stereotypes in the activities of the teacher, the positive and the negative sides of stereotyping of professional activity. Spent exploring the study showed the presence of professional pedagogical stereotypes at the school teachers and University professors. It is established, that teachers are ready to the destruction of the negative impact of stereotypes activities. The technique of «colored spectacles» for the destruction of stereotypes.
Keywords: professional-pedagogical activity of the teacher; University lecturer; teacher; pedagogical stereotypes; social stereotypes